Methods of incomplete taboo compliance in communication (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
This paper deals with the problem of taboo in communication. Thе article classifies the methods of incomplete taboo compliance on the material of Ukrainian speech practice. An attempt is made to distinguish the most frequent means of taboo avoiding in everyday communication and identify the taboo impact on the efficiency of communicative interaction.
Keywords: taboо; communication; euphemism; Internet communication